Effect of high-frequency repetitive transcranial magnetic stimulation on cognitive impairment in WD patients based on inverse probability weighting of propensity scores - Chen, Hong; Wang, Xie; Zhang, Juan; Xie, Daojun (Frontiers in Neuroscience, 2024)
Background Hepatolenticular degeneration [Wilson disease (WD)] is an autosomal recessive metabolic disease characterized by copper metabolism disorder. Cognitive impairment is a key neuropsychiatric symptom of WD. At present, there is no effective treatment for WD-related cognitive impairment. Methods In this study, high-frequency repetitive transcranial magnetic stimulation (rTMS) was used to treat WD-related cognitive impairment, and inverse probability weighting of propensity scores was used to correct for confounding factors. The Mini-Mental State Examination (MMSE), Montreal Cognitive Assessment (MoCA), Auditory Verbal Learning Test (AVLT), Boston Naming Test (BNT), Clock Drawing Test (CDT) and Trail Making Test (TMT) were used to evaluate overall cognition and specific cognitive domains. Results The MMSE, MoCA and CDT scores after treatment were significantly different from those before treatment (MMSE: before adjustment: OR = 1.404, 95% CI: 1.271–1.537; after adjustment: OR = 1.381, 95% CI: 1.265–1.497, p < 0.001; MoCA: before adjustment: OR = 1.306, 95% CI: 1.122–1.490; after adjustment: OR = 1.286, 95% CI: 1.104; AVLT: OR = 1.161, 95% CI: 1.074–1.248; after adjustment: OR = 1.145, 95% CI: 1.068–1.222, p < 0.05; CDT: OR = 1.524, 95% CI: 1.303–1.745; after adjustment: OR = 1.518, 95% CI: 1.294–1.742, p < 0.001). The BNT and TMT scores after adjustment were not significantly different from those before adjustment (BNT: before adjustment: OR = 1.048, 95% CI: 0.877–1.219; after adjustment: OR = 1.026, 95% CI: 0.863–1.189, p > 0.05; TMT: before adjustment: OR = 0.816, 95% CI: 1.122–1.490; after adjustment: OR = 0.791, 95% CI: 0.406–1.176, p > 0.05). Conclusion High-frequency rTMS can effectively improve cognitive impairment, especially memory and visuospatial ability, in WD patients. The incidence of side effects is low, and the safety is good.